Pengaruh Kepuasaan Konsumen Terhadap Perilaku Belanja Online Pada E-Commerce - Rika Astuti; Dwipo Setyantoro (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
The rapid development of Information and Communication Technology has triggered the birth of various trends in everyday life such as E-commerce activities which have now penetrated various elements of society. Online shopping activities have grown significantly in line with the increase in buying and selling activities online. This is the background of this research on the effect of online shopping transaction satisfaction and consumer trust on online shopping attitudes and behavior in E-commerce. The purpose of this study was to determine the influence of consumer satisfaction on attitudes and behavior of e-Commerce consumers. The methods used in this research are qualitative and quantitative. The findings of this study indicate that overall customer satisfaction has a stronger influence on the desire to return to online shopping and is the best indication of their desire to return to shopping on the site, among others, with the ease of ordering, product information, website performance and product suitability. ordered.